Application of the Principle of Nationality in the Ownership of Flat Units by Foreigners - Yunas, Sarah Safira; Koeswahyono , Imam; Masykur, M. Hamidi; Ikaningtyas (Faculty of Law, Universitas Brawijaya, 2025)
The regulation of space ownership, particularly for foreigners owning apartment units in Indonesia, lacks clear substance in Law No. 6 of 2023 (Omnibus Law) and its derivatives. This is due to the principle of Nationality, which is the main principle in acquiring property rights based on the Agrarian Law Policy. Although foreigners’ property ownership rights are limited, this raises conflicts as stated in Article 9 paragraph (1) of the Agrarian Law. This research employs normative juridical method with statute and conceptual approaches to address these issues. The analysis of legal materials and regulations found that the Agrarian Law asserts that foreigners can only obtain the Right to Use land. However, the Agrarian Law lacks dynamism when applied to space ownership rights. Ministry of Land Regulation No. 29 of 2016 offers a solution by limiting foreigners’ ownership of apartment units to the Right to Use Apartment Units (RIGHT TO USE A FLAT UNIT). This process differs from that for Indonesian citizens, which is based on the principle of Nationality. After this regulation was repealed, the Omnibus Law (OMNIBUS LAW) and its derivatives failed to provide concrete legal certainty and overlooked the principle of Nationality. Omnibus Law disregards the principle of Nationality and conflicts with the Agrarian Law and the Apartment Law (UU Rusun) as foundational regulations (lex specialis derogate legi generali).